Speak Up: Stepping up "show and tell" to enhance EFL students' speaking and communication skills - Betaubun, Martha; Rokhmah, Desy Eva laila (Jurnal Cakrawala Pendidikan, 2024)
As the world has shifted dramatically, university graduates must possess hard and soft skills to compete in the job market and thrive in the competitive era of 5.0. Strong communication skills, encompassing speaking, listening, observing, and empathizing, are essential for success in this competitive environment. This paper aims to elaborate on implementing a simple classroom activity called "Show and Tell" to encourage students to communicate freely. The show-and-tell activity was modified to meet the needs of university-level students. The study involved 120 students from the civil engineering, law, and architecture departments of Musamus University of Merauke, with 53 female and 67 male students. This research utilized a qualitative approach to understand the learners' development better. The data collection methods in the field included field notes, audio-video recordings, and interviews with the learners. The results indicate that while students' English competencies were generally at a beginner level, the "show and tell" activity significantly enhanced their confidence and communication skills. Participants reported feeling more at ease when speaking in front of their peers, leading to improved articulation and organization of thoughts. Simultaneously, the activity also fostered empathy and a supportive learning environment, as students connected emotionally with their classmates.